Environmental Enrichment Modifies the PKA-Dependence of Hippocampal LTP and Improves Hippocampus-Dependent Memory - Duffy, Steven N. (Cold Spring Harbor Laboratory Press, 2001)
cAMP-dependent protein kinase (PKA) is critical for the expression of some forms of long-term potentiation (LTP) in area CA1 of the mouse hippocampus and for hippocampus-dependent memory. Exposure to spatially enriched environments can modify LTP and improve behavioral memory in rodents, but the molecular bases for the enhanced memory performance seen in enriched animals are undefined. We tested the hypothesis that exposure to a spatially enriched environment may alter the PKA dependence of hippocampal LTP. Hippocampal slices from enriched mice showed enhanced LTP following a single burst of 100-Hz stimulation in the Schaffer collateral pathway of area CA1. In slices from nonenriched mice, this single-burst form of LTP was less robust and was unaffected by Rp-cAMPS, an inhibitor of PKA. In contrast, the enhanced LTP in enriched mice was attenuated by Rp-cAMPS. Enriched slices expressed greater forskolin-induced, cAMP-dependent synaptic facilitation than did slices from nonenriched mice. Enriched mice showed improved memory for contextual fear conditioning, whereas memory for cued fear conditioning was unaffected following enrichment. Our data indicate that exposure of mice to spatial enrichment alters the PKA dependence of LTP and enhances one type of hippocampus-dependent memory. Environmental enrichment can transform the pharmacological profile of hippocampal LTP, possibly by altering the threshold for activity-dependent recruitment of the cAMP-PKA signaling pathway following electrical and chemical stimulation. We suggest that experience-dependent plasticity of the PKA dependence of hippocampal LTP may be important for regulating the efficacy of hippocampus-based memory.